The ancient Balkan lakes harbor a new endemic species of Diaphanosoma Fischer, 1850 (Crustacea: Branchiopoda: Cladocera) - Korovchinsky, Nikolai M.; Petkovski, Trajan K. (Zootaxa, 2014)
Diaphanosoma macedonicum sp. nov. is described from material collected from the ancient Lakes Dojran and Prespa, located in the central part of the Balkan Peninsula. It can be regarded as a member of the “D. mongolianum” species group. It is characterized by specific, but not readily visible features, such as the absence of a thorn near the posterior valve margins, as well as setules between setae of the ventral valve inflection, and the presence of more chitinized integument. The discovery of this new species previously identified as "Diaphanosoma brachyurum (Liévin)" highlights the necessity of more detailed investigations of the zooplankton of Balkan lakes potentially populated by greater numbers of endemic cladoceran species. A short overview of the ancient lakes in the Central Balkans is provided.